(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Redox reactions, chemical reactions accompanied by a change in the oxidation numbers of atoms. The rate of oxidation does not always correspond to the strength of the oxidizing action. Conjugate oxidation by the formation of intermediate products with a higher oxidation potential in many cases is explained by the fact that an oxidizing substance (actor), acting on an easily oxidized substance (inducer), causes simultaneous oxidation of a third substance (acceptor), which itself is not oxidized or is oxidized with labor under the influence of the actor (associated reactions). This case differs from catalysis in that when the oxidation of the inductor stops, the oxidation of the acceptor stops. In typical coupled reactions it is expressed as a small integer.